Probable vertical transmission of Alpha variant of concern (B.1.1.7) with evidence of SARS-CoV-2 infection in the syncytiotrophoblast, a case report - Bullock, Hannah A.; Fuchs, Erika; Martines, Roosecelis B.; Lush, Mamie; Bollweg, Brigid; Rutan, Alyssa; Nelson, Amy; Brisso, Mark; Owusu-Ansah, Albert; Sitzman, Craig; Ketterl, Laurie; Timmons, Tim; et al. (Frontiers in Medicine, 2023)
Introduction: Definitive vertical transmission of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection has been rarely reported. We present a case of a third trimester pregnancy with fetal distress necessitating cesarean section that demonstrated maternal, placental, and infant infection with the SARS-CoV-2 Alpha variant/B.1.1.7. Methods: CDC’s Influenza SARS-CoV-2 Multiplex RT-PCR Assay was used to test for SARS-CoV-2 in a maternal NP swab, maternal plasma, infant NP swab, and formalin-fixed paraffin-embedded (FFPE) placental tissue specimens. Whole genome sequencing (WGS) was performed on maternal plasma, infant, and placental specimens to determine the SARS-CoV-2 genotype. Histopathological evaluation, SARS-CoV-2 immunohistochemistry testing (IHC), and electron microscopy (EM) analysis were performed on placenta, umbilical cord, and membrane FFPE blocks. Results: All specimens tested positive for SARS-CoV-2 by RT-PCR. WGS further revealed identical SARS-CoV-2 sequences from clade 20I/501Y.V1 (lineage Alpha/B.1.1.7) in maternal plasma, infant, and placental specimens. Histopathologic evaluation of the placenta showed histiocytic and neutrophilic intervillositis with fibrin deposition and trophoblast necrosis with positive SARS-CoV-2 immunostaining in the syncytiotrophoblast and electron microscopy evidence of coronavirus. Discussion: These findings suggest vertical transmission of SARS-CoV-2, supported by clinical course timing, identical SARS-CoV-2 genotypes from maternal, placental, and infant samples, and IHC and EM evidence of placental infection. However, determination of the timing or distinction between prepartum and peripartum SARS-CoV-2 transmission remains unclear.